REVITALISASI MASJID DI ERA MODERN (STUDI TERHADAP PERANANNYA DI ERA MODERN) - Nurul Jannah (Program Pascasarjana UIN Sumatera Utara, 2016)
This study aims to determine and understand the transformation of the role of the mosque as well as offer the revitalization of the role of the mosque at this time. This study used a qualitative approach. The results of the analysis of the study showed that the role and function of the mosque has been a change and a shift from time to time. in modern times, the mosque still felt his presence by the Muslim community. This is because the implementation of the function and role of the mosque is not maximized. Thus, this study also offers the concept of revitalizing the function and role of the mosque intact, such as the role and functions of worship, education, propaganda, economic, social, political, health and technology.